Palmyra - Sommer, Michael, 1970- author.
1 online resource (336 pages)
Keywords: "Palmyra: A History examines Palmyra, the city in the Syrian oasis of Tadmur, from its beginnings in the Bronze Age, through the classical period and its discovery and excavation, to the present day. It aims at reconstructing Palmyra's past from literary accounts '" classical and post-classical '" as well as material evidence of all kinds: inscriptions, coins, art and of course the remains of Palmyra's monumental architecture.After exploring the earliest inhabitation of Tadmur, the volume moves through the Persian and Hellenistic periods, to the city's zenith under Rome, when of all cities in the Roman empire, Palmyra was exceptional because it became a political factor in its own right when, in the 3rdcentury AD, the Roman military was overpowered by Sassanian invaders and Palmyrene troops stepped in. The assessment of Palmyra under Rome therefore considers how Palmyra could achieve such an exceptional role in the Roman Near East, before its demise under the Umayyad empire. The volume also examines the century-long history of archaeological and historical research at Palmyra, from its beginnings under Ottoman rule and the French mandate in the 1920s to the recent satellite based prospection carried out by German archaeologists. A closing chapter examines the occupation of the site by ISIS during the Syrian conflict, and the implications of the destruction there on the ruins, the archaeological finds and future investigations, and heritage in Syria more broadly. Palmyra offers academics, students and the interested reader alike the first full treatment in English of this fascinating site, providing a comprehensive account of the city's origins, rise, and fall."--Provided by publisher.